The impact of pessimistic expectations on the effects of COVID-19-Induced uncertainty in the euro area - Federico Ravenna; Gabriel Züllig; Giovanni Pellegrino (Danmarks Nationalbank, 2020)
We estimate a monthly Interacted-VAR model for euro area macroeconomic aggregates allowing for the impact of uncertainty shocks to depend on the average outlook of the economy measured by survey data. We find that, in response to an uncertainty shock, the peak decrease in industrial production and inflation is around three and a half times larger during pessimistic times. We build scenarios for a path of innovations consistent with the increase in the observed VSTOXX measure of uncertainty at the outset of the COVID-19 epidemics in February and March 2020. Industrial production is predicted to experience a year-over-year peak loss of between 15.1% and 19% in the fourth quarter of 2020, and subsequently to recover with a rebound to pre-crisis levels between May and August 2021. The large impact is the result of an extreme shock to uncertainty occurring at a time of very negative expectations for the economic outlook.
Keywords: C32; E32; 330; Current economic and monetary trends; Economic activity and employment; Models